Inhibition of BioFilm Development by Using Solanum melangena Fruit Extracts Against Some Clinically Important Pathogens - Chai, Chia Jian (2017)
Antibiotic resistance has been a global issue because generally-prescribed antibiotics are no longer effective against the resistant bacteria. One of the factors that have contributed to antibiotic resistance is the formation of biofilms. Common nosocomial pathogens such as Acinetobacter baumannii, Pseudomonas aeruginosa, Enterococci faecalis and Staphylococcus aureus are capable of forming biofilms on dry hospital surfaces, indwelling medical devices and other areas of healthcare institutions. This causes difficulties in treatment of bacterial infections and further increases the rate of mortality of patients. Thus, there is an immediate need to discover alternative biotherapeutic agents with significant antibacterial and anti-biofilm properties. This study determined the potential role of Solanum melongena in helping to overcome antibiotic resistance and biofilm development in four clinically important pathogens namely A. baumannii, P. aeruginosa, E. faecalis and S. aureus. Fruit extracts of S. melongena were prepared by using three different organic solvents including acetone, ethanol and methanol in order to compare their effectiveness in inhibiting the growth of the bacterial strains mentioned above. Phytochemical screening was also done to qualitatively determine the phenolic compounds that were contained in the three different plant extracts. Both acetone and ethanolic extracts contained flavonoids, alkaloids and tannins while only flavonoids and tannins were found in methanolic extract. Agar well diffusion assay was carried out to determine antibacterial activity of S. melongena fruit extracts against the four bacterial strains. P. aeruginosa was the only bacteria tested to be susceptible towards methanolic and ethanolic extracts whereas other bacterial isolates were resistant towards all three extracts. Subsequently, both methanolic and ethanolic fruit extracts were used in microtiter plate biofilm assay to evaluate their anti-biofilm properties on P. aeruginosa. However, biofilm size observed was not reduced by the fruit extracts. Further investigation has to be carried out to determine the effect of S. melongena in inhibiting biofilm development by testing it on a wider range of bacteria.